Juvenile Court Probation Supervised Youths: At Risk in Cuyahoga County, Ohio - Mallett, Christopher A (2006)
Focuses on the increasing court cases of juvenile delinquents which are being processed in the U.S. Average of 1.2 million youths who are adjudicated delinquent and subsequently monitored by the juvenile justice system each year; Legal implication of the term probation; Risks involved in the juvenile justice system including family conflicts, addiction disorders, school problems and trauma